2010
DOI: 10.1111/j.1551-2916.2010.03982.x
|View full text |Cite
|
Sign up to set email alerts
|

Bulk Processing of Hydroxyapatite Nanopowder Using Radio Frequency Induction Plasma

Abstract: Spherical hydroxyapatite (HA) nanopowder was synthesized at a rate of 20 g/h from HA sol using a 30 kW inductively coupled radio frequency plasma spray system. The HA sol was axially fed with a water‐cooled steel probe in the lower temperature region of the supersonic plasma nozzle, which helped in HA phase stabilization. The HA powder was synthesized at plate power between 19 and 28 kW. Particle size, surface area, particle morphology, and phase composition of the synthesized powder were evaluated using trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…The HA particles are discharged at a high speed, 510 m/s, in the lower region of the plasma arc where temperatures are relatively low and therefore, phase decomposition and amorphous phase formation is restricted due to reduced exposure to the plasma flame. Our previous studies with this nozzle have demonstrated the ability to retain high phase purity and crystallinity[25,30,33]. The XRD data, shown in Figure 1, indicates very little phase decomposition and amorphous phase formation in all samples.…”
Section: Discussionmentioning
confidence: 85%
“…The HA particles are discharged at a high speed, 510 m/s, in the lower region of the plasma arc where temperatures are relatively low and therefore, phase decomposition and amorphous phase formation is restricted due to reduced exposure to the plasma flame. Our previous studies with this nozzle have demonstrated the ability to retain high phase purity and crystallinity[25,30,33]. The XRD data, shown in Figure 1, indicates very little phase decomposition and amorphous phase formation in all samples.…”
Section: Discussionmentioning
confidence: 85%
“…The FTIR spectra of the HA, Sr‐HA, and Mg‐HA coatings are shown in Figure 2. The antisymmetric (ν 3 ) PO stretching modes of HA phosphate groups were noticed between 970 and 1190 cm −1 , whereas the PO (ν 1 ) symmetric stretching mode appeared at 960 cm −1 26, 27. The antisymmetric (ν 4 ) PO bending modes of the phosphate groups were found in the region of 540 to 660 cm −1 .…”
Section: Resultsmentioning
confidence: 92%
“…Various methodologies [ 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 ] have been used to prepare nanosized HAp with different sizes and morphologies [ 126 ]. Sol-gel [ 127 , 128 , 129 ], co-precipitation [ 130 ], wet-chemical synthesis [ 131 , 132 ], hydrothermal synthesis [ 133 , 134 ], mechano-chemical synthesis [ 135 ], mechanical alloying [ 135 ], ball milling [ 136 ], radiofrequency induction plasma [ 137 ], vibro-milling of bones [ 138 ], liquid-solid synthesis [ 139 , 140 , 141 ], electrocrystallization [ 142 ], solvothermal [ 143 ], hydrolysis of calcium orthophosphates, laser-induced fragmentation of HAp micro-particles in water, the electrospinning technique [ 144 ] and radiofrequency magnetron sputtering [ 145 ] are some of the techniques. Nano-HAp is reported [ 146 ] to have better bioactivity than microsized HAp.…”
Section: Discussion On Dense Hydroxyapatitesmentioning
confidence: 99%